Osteofibrous dysplasia arising in the humerus: A case report. (October 2018) - Yoshida, Shinichirou; Watanuki, Munenori; Hayashi, Kouu; Hosaka, Masami; Hagiwara, Yoshihiro; Itoi, Eiji; Hatori, Masahito; Hitachi, Shin; Watanabe, Mika
Osteofibrous dysplasia is a benign fibro-osseous lesion of bone which is most commonly occurred in cortical bone of anterior mid-shaft of the tibia of infancy and childhood. This study reported a case of osteofibrous dysplasia arising in the humerus of adult, resulting in good prognosis after a surgical treatment. A 34-year-old male had felt left upper arm pain and was suspected as having a bone tumor at the humeral shaft by X-ray pictures. The tumor was suspected as the osteofibrous dysplasia of the humerus by a core needle biopsy. Intralesional curettage, intraoperative anhydrous ethanol therapy, and artificial bone graft were performed. Surgical specimens showed fibro-osseous lesion, which strongly indicated osteofibrous dysplasia. Seven years after the surgery, he has lived without any local recurrence and complaints. It is important to recognize that osteofibrous dysplasia can arise in the humerus of an older patient for appropriate diagnosis.